2018
DOI: 10.21037/jtd.2018.08.144
|View full text |Cite
|
Sign up to set email alerts
|

A suspected case of inflammatory bronchial polyp induced by bronchial thermoplasty but resolved spontaneously

Abstract: T, Niimi A. A suspected case of inflammatory bronchial polyp induced by bronchial thermoplasty but resolved spontaneously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Twelve case reports and small case series reports 252 254 , 256 264 also described adverse events, including hemoptysis in seven patients, atelectasis in six patients, and lower respiratory tract infections in three patients. One individual in these reports developed a mediastinal hematoma and bloody pleural effusion while on anticoagulation therapy for a pulmonary embolism.…”
Section: Section Vii: Recommendations For the Use Of Bt To Improve Asmentioning
confidence: 94%
See 3 more Smart Citations
“…Twelve case reports and small case series reports 252 254 , 256 264 also described adverse events, including hemoptysis in seven patients, atelectasis in six patients, and lower respiratory tract infections in three patients. One individual in these reports developed a mediastinal hematoma and bloody pleural effusion while on anticoagulation therapy for a pulmonary embolism.…”
Section: Section Vii: Recommendations For the Use Of Bt To Improve Asmentioning
confidence: 94%
“…Complications from case reports with one reported occurrence included a lung abscess, an inflammatory bronchial polyp, a pulmonary cyst, and a case of bronchiectasis. [252][253][254][256][257][258][259][260][261][262][263][264] None of the 15 studies reviewed (3 RCTs and 12 case reports and case series) attributed any deaths to BT.…”
Section: Summary Of the Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…The patient received ceftriaxone, azithromycin, hydroxychloroquine and enoxaparin. After 2.5 weeks since admission his CXR showed worsening infiltrates and a bronchoscopy bronchial polyps have been reported in some inflammatory conditions for example bacterial infections and malignancy [7][8][9], we are reporting the first case of endobronchial polyps related to SARS-CoV-2 infection. A case report by Adams, et al showed multiple polyps post thermal inhalation injury which resolved after steroid course strongly indicating inflammation as primary cause.…”
Section: Case Reportmentioning
confidence: 62%